Programming Reality within the Reality-Based Interaction Framework. - Solovey, Erin Treacy.; Shaer, Orit.; Girouard, Audrey.; Hirshfield, Leanne M.; Horn, Michael S.; Zigelbaum, Jamie.; Jacob, Robert J. K. (Tufts University. Tisch Library., 2017)
In this position paper, we propose the Reality-Based Interaction (RBI) framework as a basis for analyzing, designing, and understanding organic user interfaces and transitive materials. This framework also allows us to relate these research paths to the broader domain of emerging post-WIMP interaction techniques. We believe that viewing interaction through the lens of Reality-Based Interaction (RBI) might provide insights for design and uncover gaps or opportunities for future research.